UNDERSTANDING THE DECISION OF THE CONSTITUTIONAL COURT NUMBER 90/PUU-XXI/2023 IN THE PERSPECTIVE OF CIVIL LAW AND COMMON LAW PERSPECTIVES - Lismanida; Zainal Arifin (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This research discusses the understanding of the Constitutional Court Decision Number 90/PUU-XXI/2023 in the perspective of Civil Law and Common Law. The decision has a significant impact on the Indonesian legal system, because it contains interpretations and implications that are relevant to both legal systems. significant differences which are then applied to adherent countries in accordance with the spirit of law enforcement. As for Indonesia, the use of the legal system is more inclined to the Civil law legal system even though it also implements several rules in the Common Law legal system, so that the application of the legal system in Indonesia is more suitable to be called prismatic. The results of this research are expected to contribute to the development of legal thinking in Indonesia and become an important reference for legal practitioners, academics, and policy makers in drafting or revising relevant laws.